The Complex Genetic Architecture of Early Root and Shoot Traits in Flax Revealed by Genome-Wide Association Analyses - Sertse, Demissew; You, Frank M.; Ravichandran, Sridhar; Cloutier, Sylvie (Frontiers in Plant Science, 2019)
Roots are fundamental organs for water and nutrient uptake as well as for signal transduction in response to biotic and abiotic stresses. Flax has a shallow tap root system that relies mostly on top soil nutrient and moisture resources. The crop can easily be outcompeted by weeds or other crops in intercropping systems, especially in moisture deficit conditions. However, there is a wide range of variation among genotypes in terms of performance under scarce resources such as moisture limitation. Here we phenotyped two shoot and 14 root traits on 115 flax accessions grown in a hydroponic pouch system and performed a genome-wide association study (GWAS) based on seven different models to identify quantitative trait loci underlying these traits. Significant variation among genotypes was observed for the two shoot and 12 of the 14 root traits. Shoot dry weight was correlated with root network volume, length, surface area and root dry weight (r > 0.5, P < 0.001) but not significantly correlated with root depth (r = 0.033, P > 0.05). The seven GWAS models used detected a total of 228 quantitative trait nucleotides (QTNs) the 16 traits. Most loci, defined by an interval of 100kb up and downstream of the QTNs, harboured genes known to play role(s) in root and shoot development, suggesting them as candidates. Examples of candidate genes linked to root network QTNs included genes encoding GRAS transcription factors, mitogen-activated protein kinases and auxin related lateral organ boundary proteins while QTN loci for shoot dry weight harboured genes involved in photomorphogenesis and plant immunity. These results provide insights into the genetic bases of early shoot and root development traits in flax that could be capitalized upon to improve its root architecture, particularly in view of better withstanding water limiting conditions during the cropping season.